Impact of Type of Postoperative Complications on Long-Term Survival of Gastric Cancer Patients: Results From a High-Volume Institution in China - Pang, Hua-Yang; Zhao, Lin-Yong; Wang, Hui; Chen, Xiao-Long; Liu, Kai; Zhang, Wei-Han; Yang, Kun; Chen, Xin-Zu; Hu, Jian-Kun (Frontiers in Oncology, 2021)
Background This study aimed to evaluate the impact of postoperative complication and its etiology on long-term survival for gastric cancer (GC) patients with curative resection. Methods From January 2009 to December 2014, a total of 1,667 GC patients who had undergone curative gastrectomy were analyzed. Patients with severe complications (SCs) (Clavien–Dindo grade III or higher complications or those causing a hospital stay of 15 days or longer) were separated into a “complication group.” Univariate and multivariate analyses were performed to reveal the relationship between postoperative complications and long-term survival. A 2:1 propensity score matching (PSM) was used to balance baseline parameters between the two groups. Results SCs were diagnosed in 168 (10.08%) patients, including different etiology: infectious complications (ICs) in 111 (6.66%) and non-infectious complications (NICs) in 71 (4.26%) patients. Multivariate analysis showed that presence of SCs (P=0.001) was an independent prognostic factor for overall survival, and further analysis by complication type demonstrated that the deteriorated overall survival was mainly caused by ICs (P=0.004) rather than NICs (P=0.068). After PSM, patients with SCs (p=0.002) still had a significantly decreased overall survival, and the presence of ICs (P=0.002) rather than NICs (P=0.067) showed a negative impact on long-term survival. Conclusion Serious complications, particularly of an infectious type, may have a negative impact on overall survival of GC patients. However, additional multicenter prospective studies with larger sample size are required to verify this issue.